Effects of intermittent fasting on HbA1c and weight in insulin versus oral hypoglycemic therapy-treated patients with type 2 diabetes mellitus: a systematic review and meta-analysis - Al Qudah, Jana; Beni, Newsha Davoudian; Ibrahim, Nooran; Khader, Salma; Dempsey, Laura; Butler, Alexandra E. (Frontiers in Nutrition, 2026)
AimIntermittent fasting (IF) has emerged as a beneficial dietary strategy for managing type 2 diabetes mellitus (T2DM), with improvements in certain indicators of body composition and cardiometabolic health. However, limited research compares the different effects of IF in oral hypoglycemic agents (OHAs) versus insulin-treated patients.MethodsA comprehensive search was performed across PubMed, Scopus, and Cochrane Library (January 2010–January 2025). Randomized controlled trials (RCTs) involving adults (>18-years) with T2DM undergoing IF, time-restricted feeding (TRF), alternate-day fasting (ARF), fasting-mimicking diets (FMD), and Ramadan fasting were included.ResultsIn total, 12 studies (n = 1,441 participants) met the inclusion criteria. IF improved glycemic control in both groups, with HbA1c reductions of 0.54% in OHA-users and 2.8% in insulin-users. In the meta-analysis of four eligible trials (n = 280), IF produced a significant pooled reduction in HbA1c (−1.85, 95% CI: −2.86 to −0.84), despite substantial heterogeneity (I2 = 98.1%). In contrast, IF did not produce a significant change in body weight (−1.45 kg, 95% CI: −5.51 to 2.61; I2 = 96.7%). Most studies reported weight loss, with an average body mass index (BMI) reduction of 1.53 kg/m2 in OHA users. Among insulin-users, one study reported a significant reduction in weight for the IF group (−4.77 ± 4.99 kg, p < 0.001).ConclusionIF represents an effective adjuvant therapeutic strategy in T2DM and could be widely employed in clinical practice.Systematic review registrationIdentifier CRD42025650065, https://www.crd.york.ac.uk/PROSPERO/view/CRD42025650065.